Optimal stochastic control schemes within a structural reliability framework - Leira, Bernt J. (SpringerBriefs in Statistics, 2013)
The book addresses the topic of on-line implementation of structural and mechanical design criteria as an explicit part of optimal control schemes. The intention of the present research monograph is to reflect recent developments within this area. Examples of application of relevant control algorithms are included to illustrate their practical implementation. These examples are mainly taken from the area of marine technology with the multi-component external loading being represented as both varying in time and with magnitudes that are represented as statistical quantities. The relevant target group will be mechanical and structural engineers that are concerned with "smart components and structures" where optimal design principles and control actuators are combined. The book is also  relevant for engineers e.g. involved in  mechatronics and control applications.